Contemporary issues in Islamic law - Ansari, Abdul Haseeb (Serials Publications, 2011)
This book ‘contemporary issues in Islamic law’ presents expository, sensorial and comparative study pursued by a number of legal and religions experts from different parts of the world. It falls somewhere in the whole gamut of Islamic laws. Most of the chapters of the book deal with the contemporary issues. Which are controversial and are still demanding expert critical writings. All chapters of the book might be of great contribution to the knowledge and help reaching consensus on these issues. It is for this reason that the book is relevant for researchers and policy makers.